A 100% Water Mobile Phase HPLC-PDA Analysis of Selected Neonicotinoid Insecticides (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
This paper describes a reserved-phase HPLC method for detecting frequently-used neonicotinoid insecticides, acetamiprid (ATP) and imidacloprid (ICP), using an isocratic 100 % water mobile phase.  Chromatographic separations were performed an Inertsil® WP300 C4 with water mobile phase and a photodiode-array detector.  The total run time was < 7 min.  The system suitability was well within the international acceptance criteria.  The detection limits were 0.013 μg ml-1 for ATP and 0.015 μg ml-1 for ICP, respectively.  A harmless HPLC method for simultaneous detecting ATP and ICP was developed and may be further applied to the quantification in foods.